The Cost and Utility of Postreduction Radiographs After Closed Reduction of Pediatric Wrist and Forearm Fractures. Issue 1 (January 2019) - Goodman, Avi D.; Zonfrillo, Mark R.; Chiou, Daniel; Eberson, Craig P.; Cruz, Aristides I.
Abstract : Background: Formal radiographs are frequently obtained after reduction of closed pediatric wrist and forearm fracture performed under mini C-arm fluoroscopy. However, their utility has not been clearly demonstrated to justify the increased time, cost, and radiation exposure. We hypothesized that formal postreduction radiographs do not affect the rereduction rate of pediatric wrist and forearm fractures. We further sought to determine the time, monetary, and opportunity costs associated with obtaining these radiographs. Methods: A total of 119 patients presented to our urban, level I pediatric trauma center from April 2015 to September 2015 with isolated, closed wrist and forearm fractures who underwent sedation and reduction using mini C-arm fluoroscopy. Demographic and injury variables were collected, along with incidence of rereduction and need for future surgery. Time intervals for sedation, awaiting x-ray, and total encounter periods were noted, and total direct and variable indirect costs for each encounter were obtained from our institution's cost accounting and billing databases. Marginal time and monetary costs were noted and further calculated as a percentage of the total encounter. Opportunity costs were calculated for the time spent obtaining the postreduction radiographs. Results: Of 119 patients with isolated, closed wrist or forearm fractures, none required rereduction after initial reduction using sedation and mini C-arm fluoroscopy. Postreduction radiographs required an average of 26.2 minutes beyond the end of sedation, or 7.3% of the encounter time and cost. The direct cost of the x-ray was 2.6% of the encounter cost. With our institution's annual volume, this time could have been used to see an additional 656 patients per year. Conclusions: Postreduction formal radiographs did not result in changes in management. There are significant direct and opportunity costs for each patient who undergoes additional formal radiographs. Pediatric patients with isolated, closed wrist or forearm fractures do not routinely need formal radiographs after reduction under mini C-arm fluoroscopy. Level of Evidence: Level IV—Therapeutic.